Artificial intelligence can improve decision-making in infection management - Rawson,TM; Ahmad,R; Toumazou,C; Georgiou,P; Holmes,A (Nature Human Behaviour, 2019)
Antibiotic resistance is an emerging global danger. Reaching responsible prescribing decisions requires the integration of broad and complex information. Artificial intelligence tools could support decision-making at multiple levels, but building them needs a transparent co-development approach to ensure their adoption upon implementation.